Control of brain metastases with alectinib in anaplastic lymphoma kinase‐rearranged lung cancer. Issue 3 (6th March 2017) - Kwok, Wang Chun; Tam, Terence Chi Chun; Lui, Macy Mei Sze; Lam, David Chi Leung; Ho, James Chung Man
Abstract : Brain metastasis from non‐small cell lung cancer remains a challenge to physicians. It occurs in 30% of patients with advanced stage adenocarcinoma of lung and is often regarded as the ominous sign of disease progression and death. Alectinib is likely to be a promising agent, even after the failure of crizotinib and ceritinib, for patients with anaplastic lymphoma kinase (ALK) ‐driven non‐small cell lung cancer with brain metastasis, resulting in a durable response for both intracranial and extra‐cranial diseases. Abstract : We report a young man who had ALK‐driven adenocarcinoma of lung with progressive brain metastases despite targeted therapy and chemotherapy. Salvage treatment with alectinib resulted in durable response in both systemic and intra‐cranial diseases. The rationale of therapeutic selection among various ALK tyrosine kinase inhibitors (TKI) is illustrated with this case in the era of personalized lung cancer treatment.